Stimulus-secretion coupling in pancreatic beta cells. - Ashcroft, F; Proks, P; Smith, P; Ammälä, C; Bokvist, K; Rorsman, P (1994)
Insulin secretion is triggered by a rise in the intracellular Ca2+ concentration that results from the activation of voltage-gated Ca2+ channels in the beta-cell plasma membrane. Multiple types of beta-cell Ca2+ channel have been identified in both electrophysiological and molecular biological studies, but it appears that the L-type Ca2+ channel plays a dominant role in regulating Ca2+ influx. Activity of this channel is potentiated by protein kinases A and C and is inhibited by GTP-binding proteins, which may mediate the effects of potentiators and inhibitors of insulin secretion on Ca2+ influx, respectively. The mechanisms by which elevation of intracellular Ca2+ leads to the release of insulin granules is not fully understood but appears to involve activation of Ca2+/calmodulin-dependent protein kinase. Phosphorylation by either protein kinase A or C, probably at different substrates, potentiates insulin secretion by acting at some late stage in the secretory process. There is also evidence that small GTP-binding proteins are involved in regulating exocytosis in beta cells. The identification and characterisation of the proteins involved in exocytosis in beta cells and clarification of the mechanism(s) of action of Ca2+ is clearly an important goal for the future.